116 Semi-quantitative imaging of macrophages in human carotid atherosclerotic plaques. (June 2018) - Kocsy, Klaudia; Wadanamby, Shavinthi; Tang, Kevin; Majid, Arshad; Redgrave, Jessica; Johnston, Jessica; Francis, Sheila; Kiss-Toth, Endre
Abstract : Introduction: Atherosclerosis is a pathological chronic inflammatory process where lipoprotein, cholesterol, calcium and apoptotic cells build up a lipid-rich plaque within an artery. Inflammatory cells such as macrophages are a major component of the atherosclerotic plaque and participate in all stages of plaque formation and progression. The plaque can be classified as histologically stable or unstable, depending on the extent of inflammation, composition and the thickness of fibrous cap. Macrophage subtypes within carotid plaques have been shown to be altered in unstable vs. stable plaques. Broadly, M1 macrophages are proinflammatory and promote atherogenesis as well as enhancing plaque instability. In contrast, M2 macrophages have regulatory and wound-healing properties including collagen synthesis and promote tissue repair. Detailed characterisation of these macrophage subtypes and correlative analysis with in vivo carotid plaque MRI and blood composition may lead to the identification of diagnostic markers to direct the best treatment for stroke patients. Methodology: Carotid plaques were obtained from patients undergoing carotid endarterectomy for recently symptomatic carotid stenosis. A validated clinical histology grading was used to define degree of overall plaque instability. The plaque 'shoulder' regions were identified on H and E stained sections and were deemed the regions of interest (ROI). Macrophage phenotypes within the shoulder regions were characterised with immunofluorescence (IF) microscopy. An IF protocol to simultaneously stain for M1 and M2 macrophages alongside an image acquisition and analysis strategy was then developed. We used single IF with a pan macrophage polarisation marker (CD68), and dual IF with M1 (CD86) and M2 marker (MR: Mannose Receptor). Plaques were imaged using multi-colour fluorescence microscopy (Leica AF6000). After image registration, the regions of positive staining for CD68 were overlapped with the dual staining (CD86/MR) section and the prevalence of CD86 +and MR +macrophages were measured. Results: Of the 16 collected plaques, an intact shoulder was identified in 13 samples and in these regions, macrophages were abundant. A median of 31.1% (4.5%–70.6%) macrophages stained for both M1 (CD86) and M2 (MR) markers. There was a higher prevalence of CD86 +MR + macrophages in shoulder regions from unstable versus stable plaques but this did not reach significance. Single positive M2 (MR +CD86-) cells were of higher prevalence in stable plaques. Hemosiderin-laden macrophages were also identified via their strong auto-fluorescence. Conclusions: M1 (CD86+) and dual staining (CD86 +MR+) macrophage populations were predominant in the unstable plaques whereas single positive M2 (MR +CD86-) cells were predominant in stable plaques. Future analysis on a larger number of carotid plaques is required to better understand the prevalence and potential influence of different macrophage populations on plaque instability.